2001
DOI: 10.1109/7333.948454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of initial joint position on nerve-cuff recordings of muscle afferents in rabbits

Abstract: The objective was to characterize nerve-cuff recordings of muscle afferents to joint rotation over a large part of the physiological joint range. This information is needed to develop control strategies for functional electrical stimulation (FES) systems using muscle afferent signals for sensory feedback. Five acute rabbit experiments were performed. Tripolar cuff electrodes were implanted around the tibial and peroneal divisions of the sciatic nerve in the rabbit's left leg. The electroneurograms (ENG) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…ENG recorded from peroneal and tibial nerves were dominated by the kinematics of ankle joint and the sensitivity of afferent signals were not constant [13]. ENG signals were influenced by three fundamental factors, namely, the initial position, the range of movement, and the stretch velocity.…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…ENG recorded from peroneal and tibial nerves were dominated by the kinematics of ankle joint and the sensitivity of afferent signals were not constant [13]. ENG signals were influenced by three fundamental factors, namely, the initial position, the range of movement, and the stretch velocity.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…It was shown that higher ankle stretch velocities resulted in a higher dynamic muscle spindle response, but had only marginal effect on the steady-state response provided that the ankle motion was terminated at the same position. Jensen et al [13] defined the steady-state and dynamic sensitivities of nerve responses under a small ramp-and-hold motion and investigated the influence of initial joint position on the muscle afferent signals. The results showed that the steady-state and dynamic sensitivities were largely dependent on the initial position.…”
Section: Introductionmentioning
confidence: 99%
“…However, attempts at providing graded measurements of limb-state (e.g. ground reaction force or joint position) with nerve cuff recordings have had limited success (Jensen et al 2001). In general, research towards the use of nerve cuff recordings for continuous joint-angle estimation has been limited to a single isolated joint, typically the ankle, and tested only in anesthetized animals (Cavallaro et al 2003, Jensen et al 2001, Jensen et al 2002, Micera et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…ground reaction force or joint position) with nerve cuff recordings have had limited success (Jensen et al 2001). In general, research towards the use of nerve cuff recordings for continuous joint-angle estimation has been limited to a single isolated joint, typically the ankle, and tested only in anesthetized animals (Cavallaro et al 2003, Jensen et al 2001, Jensen et al 2002, Micera et al 2001). Cavallaro et al (Cavallaro et al 2003) sought to improve continuous state estimation from nerve cuff recordings and tested several advanced signal processing methods, but reported difficulty in achieving generalization, especially for movements with large joint angular excursions.…”
Section: Discussionmentioning
confidence: 99%
“…Today sensory information has been extracted from peripheral nerves containing afferent fi bers from the skin ( Haugland et al, 1999 ;Inmann et al, 2001 ;Sinkjaer et al, 2003 ) or muscles ( Jensen et al, 2002( Jensen et al, , 2001( Jensen et al, , 2000 or bladder ( Jezernik et al, 2001( Jezernik et al, , 2000. In the fi rst two cases the recorded afferent activity was used to detect distinct events during movement.…”
Section: Example 2: Fes Control Of Paralyzed Limbs-activation Of Effementioning
confidence: 99%